Online interaction in social learning environment towards critical thinking skill: A framework - Wan Tur Tasnim Wan Husssin; Jamalludin Harun; Nurbiha A Shukor (OmniaScience, 2019)
Interaction is one of the crucial processes in online learning, which is a process derived from a common encouragement among people action that they able to utilize, store, share and construct knowledge. It is believed that the interaction among students is able to train the students to involve in active learning and enhance critical thinking skill. Recently, critical thinking is recognized as one of the 21st-century skills that students must have to do well in the community. The engagement of the students in a learning environment that supports higher-order thinking activity is the most effective approach to guide the students in developing critical thinking skills. Nevertheless, without the assistance of technology, it may be nearly impossible to ensure that all students have access to learning environments that support and develop these skills. The way students study, interact and think has been shifted due to the increasing use of technologies in learning institutions, particularly during online learning. The online platform is better when there are students interact with each other in form of social learning. Nonetheless, limited research is available on how online interaction in the social learning environment can promote students' critical thinking skill. This study utilized a theory-building method to design the framework. The purpose of the framework of this study is to assist other practitioners and researchers in applying the elements of online interaction in a social learning environment to foster students' critical thinking skill.